RITUAL KEAGAMAAN DAN TRADISI BUDAYA MASYARAKAT ALAS YANG ADA DI KABUPATEN ACEH TENGGARA - Miswar Miswar; Fadhila Husna Selian; Permata Sari; Uswatun Hasanah; Ilham Wahyudi (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
The Alas tribe is one of the tribes in Southeast Aceh Regency. The Alas tribe has many unique cultural traditions and religious rituals is one of the original cultural heritages of Indonesia. One of the traditional cultural traditions of the Alas tribe is Pemamanen. Pemamanen is a traditional parade (a ritual of male circumcision or marriage). The method in this study uses a descriptive method with qualitative data. The purpose of this study is to find out how the cultural traditions of the Alas people in Southeast Aceh are. The result of this research is the discovery of one of the cultural traditions of the Alas tribe, namely Pemamanen.